2009
DOI: 10.1100/tsw.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Etiologies for Phenotypic Diversity in Sickle Cell Anemia

Abstract: The clinical course of patients with sickle cell anemia, a Mendelian trait, is characteristically highly variable. HbF concentration and the presence of a thalassemia are established modulators of the disease, but cannot account for all of its clinical heterogeneity. To find additional genetic modulators of disease, genotype-phenotype association studies, where single nucleotide polymorphisms (SNPs) in candidate genes are linked with a particular phenotype, have been informative. SNPs in several genes of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 117 publications
2
128
0
9
Order By: Relevance
“…The Cameroon haplotype has previously been associated with poor clinical outcome and increased stoke episodes in SCD (Adorno et al, 2008;Steinberg et al, 1998), whereas the Benin haplotype is thought to confer a relatively favorable clinical outcome (Steinberg, 2009). In a previous report, we anticipated that the relatively high prevalence of stroke in SCD patients in Cameroon could be attributed to the high proportion of Cameroonian haplotype (Njamnshi et al, 2006).…”
Section: Fig 2 Global Distribution Of Haplotypes Among Various Worlmentioning
confidence: 97%
See 1 more Smart Citation
“…The Cameroon haplotype has previously been associated with poor clinical outcome and increased stoke episodes in SCD (Adorno et al, 2008;Steinberg et al, 1998), whereas the Benin haplotype is thought to confer a relatively favorable clinical outcome (Steinberg, 2009). In a previous report, we anticipated that the relatively high prevalence of stroke in SCD patients in Cameroon could be attributed to the high proportion of Cameroonian haplotype (Njamnshi et al, 2006).…”
Section: Fig 2 Global Distribution Of Haplotypes Among Various Worlmentioning
confidence: 97%
“…Four haplotypes are associated with HbS in Africa (Benin, Bantu/Central African Republic (CAR), Senegal, and Cameroon) and the fifth is thought to have arisen in India and/or the Arabian Peninsula (Arab/Hindu) (Elion et al, 1992;Pagnier et al, 1984). It has been suggested that these haplotypes also have an effect on the severity of the disease (Asultan et al, 2012;Steinberg, 2009) and possibly the clinical response to hydroxyurea (Friedrisch et al, 2008)-currently the only available treatment for SCD. Furthermore, these haplotypes have a well-defined geographic distribution in Africa, making it possible to establish the origin of African-descendant populations in America (Pagnier et al, 1984;Serjeant, 1989), but also the origin of SCD among Europeans from Mediterranean regions.…”
mentioning
confidence: 99%
“…Within the hemoglobin S genotype, haplotypes of the S gene appear to be related to specific phenotypes of the disease, including pain phenotypes. 50 …”
Section: Genetic Predictorsmentioning
confidence: 99%
“…Elevated Hb F levels are known to improve the clinical manifestations of the two largest known hemoglobin changes: sickle cell disease and β-thalassemia. In sickle cell disease, the Hb F concentration and distribution among the red blood cells are the main genetic modulators of the disease, whereas high levels of this hemoglobin dilute the amount of Hb S, inhibiting or delaying the polymerization process, which results in reduced disease severity (Steinberg, 2009). In homozygous β-thalassemia, increased production of γ chains helps in re-γ chains helps in reducing the imbalance of α and non-α chains and increasing total hemoglobin levels (Galanello and Cao, 1998;Thein, 2005).…”
Section: Introductionmentioning
confidence: 99%